Profil Pengajaran Guru Matematika terhadap Kemampuan Pengelolaan Kelas Berbasis Rencana Kegiatan Belajar Mengajar (RKBM) pada Materi Pertidaksamaan Rasional - Mukminin, M. Nashihul; Amelia, Riska Putri; Haq, Rafli Fayzul; Rofiki, Imam (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
Good classroom management is very necessary for teachers to achieve learning objectives. However, previous research states that classroom management in the implementation of mathematics learning on rational inequality material is still less than optimal. This is caused by the lack of the teacher's ability to manage the class. As a result, students are less interested in participating in learning activities. Therefore, this study aims to describe the teaching profile of mathematics teachers on classroom management skills on rational inequality material based on the Teaching and Learning Activity Plan (RKBM). This research uses descriptive research with a qualitative approach. The participants of this study were a mathematics teacher of MAN 2 Malang City and 36 students of S1 IPS-1 (Grade 10). Data collection techniques were observation, interview, and documentation. Data analysis techniques were carried out in several stages, namely data collection, data condensation, data presentation, and conclusion drawing. The results showed that RKBM-based mathematics teacher teaching could support good classroom management including, the majority of students being enthusiastic in participating in learning activities and students orderly carrying out the instructions given by the teacher. The results of this study can be used as a reference for teachers to design creative and interactive learning activities